Procedure Choice in Primary Versus Recurrent Prolapse: A Study of Fellowship-Trained Surgeons. Issue 4 (July 2018) - High, Rachel; Kavanagh, Alex; Khavari, Rose; Stewart, Julie; Antosh, Danielle D.
Abstract : Objective: This retrospective study describes procedures of choice in management of patients with primary prolapse compared with recurrence prolapse patients by fellowship-trained surgeons. Methods: Surgically managed primary and recurrent prolapse cases from 2012 to 2015 at Houston Methodist Hospital were reviewed. Baseline characteristics, compartment defects, and stage were compared. Mean interval from the index surgeries to management of prolapse recurrence was recorded. In recurrence cases, mesh complaints were noted if present. Primary outcome was the procedure type used to manage cases of recurrence and primary prolapse. Logistic regression was used to determine odds ratio (OR) for the procedure of choice in recurrence and primary repairs of prolapse. Results: Of 386 cases reviewed, 379 met criteria for inclusion; 25.8% of repairs were for recurrence. Recurrence patients were significantly older than primary cases (mean, 63.6 vs 60.5; P = 0.03) and had been postmenopausal for longer ( P = 0.004). Median time interval to surgical management of recurrence was 8 years. Thirty percent of recurrence patients treated previously by mesh had mesh complaints. There was no difference in the distribution of defects or stage. Sacrocolpopexy was more frequently used to manage recurrent prolapse (OR, 2.6334; P < 0.0005). Vaginal mesh repairs showed no difference in utilization. Uterosacral ligament fixation (OR, 0.347; P = 0.002) was used more often in primary prolapse. Anterior colporrhaphy (OR, 0.398; P = 0.0005) and uterosacral ligament fixation (OR, 0.347; P = 0.002) were performed less in recurrence cases. Conclusion: Fellowship-trained urogynecologists at this institution utilize sacrocolpopexy mesh more frequently in recurrent prolapse, and uterosacral ligament fixation was used more frequently in primary prolapse cases. Abstract : This retrospective study describes procedures of choice in management of primary prolapse compared to recurrence prolapse by fellowship-trained surgeons at a single institution.